Композиційна високопориста теплова ізоляція з ефективними параметрами пористості - Павленко, Анатолій Михайлович; Чейлитко, Андрій Олександрович; Носов, Максим Андрійович (НТУ "ХПІ", 2016)
Виконано емпіричні дослідження композиційного матеріалу, складовими частинами якого є вогнетривка вата вкрита тонким шаром алюмінію та алюмінієва фольга. Для покращення теплофізичних властивостей композиційного матеріалу в ваті були зроблені комірки параболоїдної форми після чого на деформовану поверхню нанесено тонкий шар алюмінію. Загальна ширина експериментальних зразків складала 5 мм. За допомогою методу планування експерименту знайдено оптимальні геометричні розміри комірок, при яких досягається коефіцієнт теплопровідність 0,226 Вт/(м∙К).

In this work, thermal insulation material which consists of the fireproof wool covered by a thin aluminum layer and the aluminum foil was investigated. The objective was to determine effective porosity parameters for composite heat insulation by which a minimum thermal conductivity will be obtained. According to the objective, following tasks were formulated: make the empirical research with different porosity parameters; find regression equation of dependence of the material thermal conductivity on the geometric dimensions; analyze and verify the importance of factors; obtain the optimal porosity parameters for composite heat insulation material. To improve the thermal properties of the composite material, in the wool were made cells with paraboloid shape and then surface was covered by thin layer of aluminum. Cells were made by pressing method. The total width of the experimental samples was 5 mm. The depth of the cell was 4 mm, thickness of the aluminum foil was 0,2 mm. The thermal conductivity of the material was measured using a thermal conductivity meter IT-λ-400. The optimal geometric values of the cell in composite material were obtained by the regulatory simplex algorithm (cell length 7,6074 mm, cell thickness 12,534 mm). At the optimal geometric values, the following thermal conductivity coefficient was achieved – 0,226 W/(m∙K). Set tasks were completed in full The obtained results can be introduced into existing production technologies of composite sandwich panels, for example in the sandwich panels by Rockwool company. Also it can be serve as a basis for the development of more modern materials. Composite materials with such cell structure will be more effective in comparison with usual non cell materials
Compositional highly porous thermal insulation with effective porosity parameters
Keywords: композиційний матеріал; вогнетривка вата; алюміній; комірки; коефіцієнт теплопровідності; composite material; fireproof wool; aluminum; cell; thermal conductivity